Postgraduate study: the hidden cost of writing a thesis - Scheffer, Judi (Massey University, 2002)
Not too many years ago the attitude that: "Women are no good at mathematics, as it is a logical subject which requires a rational mind. As women are irrational, therefore they will not succeed at mathematics or understand it, and therefore should not be encouraged to study it." (McKenzie, 2001) prevailed. Many of these attitudes are fading, but still unseen hurdles exist.
Keywords: Sexism in mathematics study; Postgraduate study